Conformational changes of ubiquitin during electrospray ionization as determined by in‐ESI source H/D exchange combined with high‐resolution MS and ECD fragmentation. (29th September 2014) - Kostyukevich, Yury; Kononikhin, Alexey; Popov, Igor; Nikolaev, Eugene
<x xml:space="preserve">Abstract</x> In the paper, we have demonstrated the possibility of performing hydrogen/deuterium (H/D) exchange of proteins in the region of gas‐phase ion formation in an electrospray ion source by saturating the electrospray ionization source with vapors of a deuterating agent (D2O or MeOD). In this region, charged droplets are shrinking and the protein ions transfer into the gas phase. As a model protein, we have used ubiquitin whose ion mobility spectrometry and gas‐phase H/D exchange in the vacuum part of a mass spectrometer demonstrated the presence of gas‐phase conformers with different cross sections and H/D exchange rates. In our experiments, we observed monomodal deuterium distributions for all solvents, charge states, desolvating capillary temperature and types of deuterating agent. Also, we found that the number of H/D exchanges increases with an increasing desolvating capillary temperature and decreasing charge state. We observed that solution composition (49 : 50 : 1 H2O : MeOH : formic acid or 99 : 1 H2O : formic acid) influences the charge‐state distribution but did not change the degree of H/D exchange for the same charge state. Electron‐capture dissociation fragmentation shows that higher charge states contain a segment that is protected from access by the deuterating agent. Copyright © 2014 John Wiley & Sons, Ltd.